Sistem Komunikasi Pengembangan Literasi Budaya Batak Toba di Rumah Belajar Sianjur Mulamula - Elisabet Marthawati Samosir (Jurnal Media dan Komunikasi Indonesia, 2023)
The communication system in the view of Niklas Luhmann is an orientation between systems in an environment to respond to complexity in an environment. Initially Rumah Belajar Sianjur Mulamula as an environment formed a communication system as a response of various systems to the complexity that occurred. The system formed is in accordance with the quintuple helix, namely the education system, economic system, natural environment system, culture-based and media based society system, and political system. The systems that respond most actively are the education system and the economic system. The complexity in the Rumah Belajar Sianjur Mulamula, at first, can be seen from the main conflict that arose due to the shift in the main value of the learning house, namely the educational system to become the interests of the economic system. The complexity is getting higher due to other systems not responding to balance the communication system. This study is a qualitative research with a descriptive approach. The theory used is Niklas Luhmann's system theory. To obtain data, researchers conducted interviews by participant observation.